Institutions and Dissent: Historical Geology in the Early Royal Society - Sacco, Francesco G. (Teorie vědy / Theory of Science, 2014)
Institutions and Dissent: Historical Geology in the Early Royal Society Abstract: The paper aims to ques- tion the traditional view of the early Royal Society of London, the oldest scientific institution in continuous existence. According to that view, the institutional life of the Society in the early decades of activity (1660s and 1670s) was characterized by a strictly Baconian methodology. But the re- construction of the discussions about fossils and natural history within the Society shows that this monolithic image is far from being correct. Despite the persistent reference to the Baconian Solomon House, the Society did not impose or support a common programme of research in the field of the natural history of the Earth. Keywords: Royal Society; historical geology; experimental philosophy; Robert Hooke Instituce a disent: historická geologie v počátcích Royal Society Abstrakt: Text si klade za cíl zpochybnit tradiční pohled na ranné období londýnské Royal Society, nejstarší kontinuálně fungující vědecké instituce. Podle tradičního pohledu byl institucionální život v počátečních desetiletích vývoje Royal Society (šedesátá a sedmdesátá léta 17. století) charakterizován přijetím striktně baconovské metodologie. Rekonstrukce debat o fosiliích a přírodní historii v rámci Royal Society však ukazuje, nakolik je tento monolitický obraz vzdálený skutečnosti. Navzdory trvalým od- kazům k baconovské Šalamounově koleji Royal Society nerozvinula ani nepodporovala společný výzkumný program v oblasti přírodní historie Země. Klíčová slova: Royal Society; historická geologie; experimentální filosofie; Robert Hooke